(untitled) (CIPEEX, 2025)
Introduction: With the growing demand for practical solutions for managing sports facilities, the Sports Brazil app emerges as an essential innovation. It simplifies access to courts and sports areas through an intuitive digital platform, featuring online booking and automated processes, transforming the experience for users and owners in the sports world. Objective: The Sports Brazil app aims to simplify and optimize access to the sports world, promoting leisure and well-being. Method: It operates through an online booking system for courts and private sports areas, with intuitive interfaces, automated reservation processes, and integrated payment systems, eliminating the need for direct contact with the owner and streamlining the entire process. Result: The app enhances user experience, increases bookings and court occupancy, benefiting both owners and users. Additionally, it optimizes management by reducing time spent on customer service and ensuring customer loyalty to the system. Conclusion: The implementation of a reservation app for sports spaces transforms the user experience and improves facility management by automating processes, increasing operational efficiency, enhancing occupancy, and generating new revenue. With a modern and convenient solution that meets customer expectations, the app becomes an essential tool for optimizing the operation and success of sports facilities, focusing on practicality, security, and user experience.